Targeting cancer hallmarks using resveratrol: isolation, formulation, and mechanisms of action - Talib, Wamidh H.; Al Junaidi, Hadeel Shaher; Hadi, Rawan W.; Ashour, Tassneem H.; Zabout, Islam Z.; Sabri, Suha M.; Alshaeri, Heba K.; Law, Douglas; Hock, Márta; Prémusz, Viktória (Frontiers in Nutrition, 2026)
Natural products, particularly medicinal plants, play a crucial role in combating cancer and developing new treatments due to their unique properties, such as diverse chemical structures, low toxicity, and the ability to target various types of cancer. They offer a promising approach for the treatment and prevention of certain cancers. Resveratrol, a non-flavonoid polyphenolic compound found in several plants, has demonstrated beneficial effects on various diseases, including cancer, as evidenced by numerous studies. It may also help address multiple cancers by influencing their growth and metastasis. One proposed mechanism is that resveratrol reduces reactive oxygen species (ROS) and lipid peroxidation by activating the JNK/c-JUN signaling pathway, which enhances the expression of antioxidant enzymes. Additionally, resveratrol has been shown to regulate cell proliferation by suppressing the PI3K/Akt pathway and activating the SIRT1 pathway. Other mechanisms include the inhibition of NF-κB activation and the downregulation of downstream proteins such as MMP-9, CXCR4, and FAK, which are known to facilitate metastasis. Furthermore, resveratrol inhibits Akt phosphorylation, and inhibition of PI3K or mTOR mimics its effects on glucose uptake. This review discusses these mechanisms, emphasizing the anticancer properties of resveratrol and its role in various aspects of cancer, supported by research on the compound’s formulation and clinical studies involving this natural agent.